A Qur’anic Management Framework for Sustainable Work Ethics in the Digital Era: Operationalizing Amānah and Integrity for Organizational Resilience - Akilah, Fahmiah; Abu Bakar, Achmad; Mafuz, Muhsin (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2026)
Purpose –This study addresses the ethical erosion and dehumanizing tendencies of digitally mediated work (e.g., algorithmic control, gig arrangements, and transactional performance pressures) by formulating a Qur’anic management framework for sustainable work ethics grounded in amānah and integrity. It responds to the gap between prevailing digital work norms and Qur’anic moral ideals, with a focus on long-term organizational sustainability. Methods – Using a tafsīr maudhū‘ī (thematic) approach within qualitative library research, the study conducts a structured thematic synthesis: (i) selection of Qur’anic passages relevant to work, trust, justice, and responsibility; (ii) contextual reading through classical and contemporary tafsīr; and (iii) hermeneutic translation of ethical themes into management constructs and sustainability-oriented outcomes (governance, social well-being, and responsible conduct). Findings–The study constructs an integrative model comprising three pillars—al-‘adl (justice), al-amānah (trustworthy integrity), and mas’ūliyyah ijtimā‘iyyah (social responsibility)—operationalized as sustainability enablers in digital workplaces. Al-‘adl supports fair treatment and worker well-being in data-driven performance systems; al-amānah strengthens ethical governance and accountability under automation; and mas’ūliyyah ijtimā‘iyyah matches organizational behavior with collective benefit and CSR-like commitments. Practical Implications–The framework offers a sustainability-oriented paradigm for human resource management, ethical leadership, and organizational governance, enabling firms to mitigate digital-era risks by embedding justice, integrity, and collective responsibility into codes of ethics, evaluation systems, and digital-work policies. Originality/value–This study advances Islamic management scholarship by moving beyond normative exposition to propose an operational Qur’anic management framework that links Qur’anic ethics to sustainability outcomes in contemporary digital organizations